A polymorphic MYC response element in KBTBD11 influences colorectal cancer risk, especially in interaction with an MYC-regulated SNP rs6983267. (18th December 2017) - Gong, J; Tian, J; Lou, J; Wang, X; Ke, J; Li, J; Yang, Y; Gong, Y; Zhu, Y; Zou, D; Peng, X; Yang, N; et al.
Abstract: Background: MYC is a well-established cancer driver gene regulating the expression of numerous genes, indicating that polymorphisms in MYC response elements could affect tumorigenesis through altering MYC regulation. We performed integrative multistage study to evaluate the effects of variants in MYC response elements and colorectal cancer (CRC) risk. Patients and methods: We systematically integrated ChIP-Seq, DNase-Seq and transcription factor motif data to screen variants with potential ability to affect the MYC binding affinity. Then, we conducted a two-stage case–control study, totally consisting of 4830 CRC cases and 4759 controls in Chinese population to identify risk polymorphisms and interactions. The effects of risk variants were confirmed by functional assays in CRC LoVo, SW480 and HCT15 cells. Results: We identified a novel polymorphism rs11777210 in KBTBD11 significantly associated with CRC susceptibility ( P  = 2.43 × 10 −12 ). Notably, we observed a significant interaction between rs11777210 and MYC nearby rs6983267 ( P -multi  = 0.003, P -add  = 0.005), subjects carrying rs6983267 GG and rs11777210 CC genotypes showing higher susceptibility to CRC (2.83-fold) than those carrying rs6983267 TT and rs11777210 TT genotypes. We further demonstrated that rs6983267 T > G increased MYC expression, and MYC bound to and negatively regulated KBTBD11 expression when the rs11777210 C risk allele was present. KBTBD11 was downregulated in tumor tissues, and KBTBD11 knockdown promoted cell proliferation and inhibited cell apoptosis. Conclusion: The rs11777210 is a potential predictive biomarker of CRC susceptibility, and KBTBD11 functions as a putative tumor suppressor in tumorigenesis. Our study highlighted the high CRC risk of people carrying rs6983267 G and rs11777210 C alleles, and provided possible biological mechanism of the interaction.